On the substitution effect of board capital as a governance mechanism in emerging markets: Evidence from Latin-America (2019)
This paper analyzes the substitution effect of board capital as corporate governance mechanism on firm performance proxied by Tobin¿s Q under the context of weak legal regime for investor protection. The study focuses on Latin America as a representative emerging market that includes a dataset of 442 firms in 6 countries (Argentina, Brazil, Chile, Colombia, Mexico, and Peru) from 2001 to 2012. We measure board capital as a composite index of directors¿ educational attainment and professional experience. We find a positive relationship but with differential effects between board capital and firm performance within weak firm internal governance schemes such as firms with low board independence, dual roles as firm CEOs and COBs, and low blockholder contestability. Also analyzing country level governance standards, we find that as long there are improvements in country¿s regulatory quality, rule of law, and corruption control the less the need for firm board capital as an internal governance mechanism.